2020
DOI: 10.1074/jbc.ra119.012351
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the extracellular domains of human interleukin 11α receptor reveals mechanisms of cytokine engagement

Abstract: Interleukin (IL) 11 activates multiple intracellular signaling pathways by forming a complex with its cell surface α-receptor, IL-11Rα, and the β-subunit receptor, gp130. Dysregulated IL-11 signaling has been implicated in several diseases, including some cancers and fibrosis. Mutations in IL-11Rα that reduce signaling are also associated with hereditary cranial malformations. Here we present the first crystal structure of the extracellular domains of human IL-11Rα and a structure of human IL-11 that reveals p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(78 citation statements)
references
References 77 publications
4
74
0
Order By: Relevance
“…Likewise, the IL-11Rα binding site (site-I) and the first gp130 binding site (site-II) of IL-11, previously identified through mutagenesis (175,176), are different in chemical character to IL-6, with site-I more hydrophobic (Figure 6B). Our recent structure of IL-11Rα ( Figure 6C) (174) revealed that the cytokine binding site of the receptor is more hydrophobic in character than IL-6Rα, consistent with the corresponding site of IL-11 and suggesting distinct mechanisms of cytokine engagement.…”
Section: Structure Of Il-11 and Its Receptorssupporting
confidence: 63%
See 4 more Smart Citations
“…Likewise, the IL-11Rα binding site (site-I) and the first gp130 binding site (site-II) of IL-11, previously identified through mutagenesis (175,176), are different in chemical character to IL-6, with site-I more hydrophobic (Figure 6B). Our recent structure of IL-11Rα ( Figure 6C) (174) revealed that the cytokine binding site of the receptor is more hydrophobic in character than IL-6Rα, consistent with the corresponding site of IL-11 and suggesting distinct mechanisms of cytokine engagement.…”
Section: Structure Of Il-11 and Its Receptorssupporting
confidence: 63%
“…In contrast to IL-6, LIF and other IL-6 family cytokines, little was previously known about the structure of IL-11 or IL-11Rα. We reported the first crystal structure of IL-11 in 2014 (98) and have recently reported a higher-resolution structure of the cytokine (Figure 6A) (174). Our structures show that IL-11 is ∼5 Å longer than IL-6, suggesting differences in binding mode and geometry within the signaling complex.…”
Section: Structure Of Il-11 and Its Receptorsmentioning
confidence: 60%
See 3 more Smart Citations